Taxes, keiretsu affiliation, and income shifting - Gramlich, Jeffrey D.; Limpaphayom, Piman; Ghon Rhee, S. (Journal of Accounting and Economics, 2004)
This paper provides evidence that keiretsu group member firms are subject to lower effective tax rates than independent firms in Japan. As an explanation, we develop a hypothesis that keiretsu firms strategically shift financially reported income among affiliates in order to reduce overall effective tax rates. Empirical evidence supports this income-shifting hypothesis since the positive relation between pre-tax return on firm value and marginal tax rate status is significantly mitigated by keiretsu membership. Contrasting conjecture, keiretsu income-shifting activities intensify when Japanese firms face economic recession. The evidence also suggests that benefactors of shifted income are compensated via increased dividends.